Preliminary study of anti-CD40 and ubiquitin proteasome antibodies in primary podocytopaties - Chebotareva, Natalia; Cao, Venzsin; Vinogradov, Anatoliy; Alentov, Igor; Sergeeva, Natalia; Kononikhin, Alexey; Moiseev, Sergey (Frontiers in Medicine, 2023)
Background Minimal change disease and focal segmental glomerulosclerosis are primary podocytopathies that are clinically presented in adults presenting with severe nephrotic syndrome. The pathogenesis of these diseases is not clear and many questions remain to be answered. A new concept about the role of changes in the antigenic determinant of podocytes and the production of anti-podocyte antibodies that cause podocyte damage is being developed. The aim of the study is to evaluate the levels of anti-CD40 and anti-ubiquitin carboxyl-terminal hydrolase L1 (anti-UCH-L1) antibodies in patients with podocytopathies in comparison with other glomerulopathies. Methods One hundred and six patients with glomerulopathy and 11 healthy subjects took part in the study. A histological study revealed primary FSGS in 35 patients (genetic cases of FSGS and secondary FSGS in the absence of NS were excluded), 15 had MCD, 21 - MN, 13 - MPGN, 22 patients - IgA nephropathy. The effect of steroid therapy was evaluated in patients with podocytopathies (FSGS and MCD). The serum levels of anti-UCH-L1 and anti-CD40 antibodies were measured by ELISA before steroid treatment. Results The levels of anti-UCH-L1 antibodies were significantly higher in MCD patients and anti-CD40 antibodies were higher in MCD and FSGS than in the control group and other groups of glomerulopathies. In addition, the level of anti-UCH-L1 antibodies was higher in patients with steroid-sensitive FSGS and MCD, and anti-CD40 antibodies were lower than in patients with steroid-resistant FSGS. An increase in anti-UCH-L1 antibody levels above 6.44 ng/mL may be a prognostic factor of steroid-sensitivity. The ROC curve (AUC = 0.875 [95% CI 0.718–0.999]) for response to therapy showed a sensitivity of 75% and specificity of 87.5%. Conclusion An increase in the level of anti-UCH-L1 antibodies is specific for steroid-sensitive FSGS and MCD, while an increase in anti-CD40 antibodies – for steroid-resistant FSGS, compared with other glomerulopathies. It suggests that these antibodies could be a potential factor for differential diagnosis and treatment prognosis.